Centrifugal compressors for He circulation loops for ITER. (April 2019) - Kouzmenko, G; Simon, M; Saulquin, S; Buskop, J; Voigt, T; Grillot, D; Ferioli, M; Feraille, D
Abstract: Thermal shields of ITER machine and cryopumps are cooled by two forced-flow helium cooling loops using helium at 80 K as a cooling media and liquid nitrogen as a source of cooling. Two-stage integrally geared centrifugal compressors provide mass flow of up to 4 kg/s per each machine with a suction and discharge pressure of 1.6 and 1.8 MPa correspondingly. This is the first in the world use of such machines for helium, and therefore an extensive testing program was developed to demonstrate as much as possible that the required performance is achieved. This paper presents the details of chosen construction of machines, as well as explains particularities of using centrifugal compressors for He and specific problems which were required to be solved, in particular to meet strict leak tightness requirements and overcome rotordynamics issues. Factory testing program and achieved results regarding machines' performance and treatment of shaft seal leaks are also described.